Analytic Loss Minimization: Theoretical Framework of a Second Order Optimization Method - Ioannis K. Dassios (Symmetry, 2019)
In power engineering, the <semantics> Y b u s </semantics> is a symmetric <semantics> N × N </semantics> square matrix describing a power system network with N buses. By partitioning, manipulating and using its symmetry properties, it is possible to derive the <semantics> K G L </semantics> and <semantics> Y G G M </semantics> matrices, which are useful to define a loss minimisation dispatch for generators. This article focuses on the case of constant-current loads and studies the theoretical framework of a second order optimization method for analytic loss minimization by taking into account the symmetry properties of <semantics> Y b u s </semantics> . We define an appropriate matrix functional of several variables with complex elements and aim to obtain the minimum values of generator voltages.